Teachers' turnover and their job satisfaction at basic education school in some regions in Oman: Structural equation modelling approach - Amzat, Ismail Hussein; Neimi, Rawdha Khalfan Rashid Al (Inderscience Publishers, 2014)
This research examines the factors that lead to job satisfaction which can also cause dissatisfaction among the basic education teachers in selected regions at Al-Dzahira, Al-Dakhelya and Muscat in the Sultanate of Oman.It investigates the causes behind the teacher’s low interest towards the teaching profession and the reasons behind the teachers’ unfavourable turnover in these regions.Questionnaires were distributed to 223 selected teachers in the basic education schools in these regions. The principal component analysis was used to determine the best items across their factors and the measurement model for the model-fit as well as indicators and predictors. The path analysis was applied to know the direct-effect of the exogenous on endogenous variables.From the results of factor analysis, it shows that the ‘teaching load’ factor seemed to have the highest item loading followed by the ‘salary’ and the ‘promotion/recognition’ also had very strong items loadings that should be fairly considered.CFA tests also confirmed the same results where the issues related to teaching are the first factors followed by the salary and the promotion that led to the teachers’ turnover and dissatisfaction.The path analysis indicated a direct causality of teaching load and promotion on turnover.